Temporary migration as a mechanism for lasting cultural change: Evidence from Nepal - Sarah Janzen; Savannah Noray (IZA Journal of Development and Migration, 2021)
When a husband migrates, his wife may control more household resources and therefore change how the household spends income. Given the prevalence of seasonal migration in developing countries, even these temporary changes could affect economic development. The extent to which these changes persist after migration spells will magnify these consequences. Using panel data on rural households in Nepal, we examine how a husband's migration interacts with intrahousehold decision-making and consumption patterns both during and after migration spells. We find that a husband's absence is associated with a 10 percentage point increase in the expenditure decisions over which the wife has full control. This coincides with a shift away from expenditures on alcohol and tobacco in favor of children's clothing and education. Importantly, we find that migrant husbands resume their role in decisions following their return, but decisions are more likely to be made jointly. These persistent effects are consistent with a model in which households are pushed to a new, more-equitable equilibrium and then are driven to form habits, which, in turn, cause the new equilibrium to stick, thus facilitating long-term cultural change in gender norms.
Keywords: O150; D130; F220; J160; 330; migration; decision-making; bargaining power; household economics; gender